Implementation of the Independent Campus Learning Program in creating a place for creativity at SD 068004 Medan City - Amelia Putrisari; Fajar Utama Ritonga; Mujahid Widian Saragih (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
This research is entitled "Implementation of the Independent Campus Learning Program in Creating a Place for Creativity in SD 068004 Medan City." The problem that occurs is the lack of awareness about creating a place for creativity for students in elementary schools. This study uses a qualitative method. By conducting observations at the location where the Campus Teaching Program was assigned, namely SD 068004 Simalingkar, Kec. Medan Tuntungan. Observation techniques include interviews and documentation, by conducting direct observations at SD 068004, as well as conducting interviews with teacher educators and students at SD 068004 Simalingkar, Kec. Field of Benefits. The research results show that education is a basic and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals and skills that are needed by themselves, society, and country. So there is a need for a forum for students to channel their interests and talents and develop them in order to train their creativity and skills in the learning process at school. With this research, the researcher hopes to improve the quality of student learning at SD 068004 and create a place for creativity for students to develop.